Adjuvant platinum-based chemotherapy in non-small cell lung cancer: The role of relative dose-intensity and treatment delay. (2021) - Szejniuk, WM; Cekala, M; Bøgsted, M; Meristoudis, C; McCulloch, T; Falkmer, UG; Røe, OD
Highlights: Adjuvant cisplatin relative dose intensity (RDI) is associated with survival. Less than four courses of adjuvant chemotherapy is detrimental for survival. Performance status 1 patients treated with low RDI had inferior overall survival. Squamous carcinoma patients treated with high RDI had longer disease-free survival. Adjuvant chemotherapy given > 6 weeks after surgery had no impact on survival. Abstract: Background: The study investigated the association of the relative dose-intensity (RDI) of cisplatin and timing of adjuvant platinum-based chemotherapy (APC) with survival for stage I-III non-small cell lung cancer (NSCLC) patients. Material and Methods: Real-life data of patients treated with APC (four cycles of cisplatin and vinorelbine) between 2007 and 2014 was included to analyse the association between disease-free survival (DFS) and overall survival (OS) with RDI (ratio of received to planned dose-intensity). High RDI was defined as cisplatin RDI of > 75% and low RDI ≤ 75%. Results: Out of 198 patients, 166 were eligible. Low RDI was administered to 72 (43%) patients. In multivariate analysis, those patients had a significantly higher risk of recurrence (HR: 1.87, 95%CI 1.13–3.09, p  = 0.01) and death (HR: 1.91, 95%CI 1.32–3.23, p  = 0.01) versus patients in the high RDI group. The risk of death was significantly higher in patients with PS 1 treated with low versus high RDI (HR: 2.72, 95%CI: 1.22–6.09, p  = 0.014). The risk of recurrence was higher for patients with squamous cell carcinoma of low versus high RDI (HR: 3.82, 95%CI: 1.01–14.4, p  = 0.048). No impact of delayed APC beyond six weeks from surgery on neither DFS (HR: 0.78, 95%CI: 0.46–1.33, p  = 0.36) nor OS (HR 0.67, 95%CI: 0.40–1.15, p  = 0.15) was observed. Conclusion: Low cisplatin RDI ≤ 75% of APC, but not extended time from surgery to APC onset > six weeks, was associated with significantly shorter survival in NSCLC patients.